Collaborative Learning to Foster Critical Reflection by Pre-service Student Teachers within a Canadian-South African Partnership - Corné Kruger; Jan Buley (University of Windsor, 2022)
Teachers often enter practice with a narrow perspective of teaching. Through critical reflection, the minds of pre-service teachers can be opened to the bigger realities of teaching and social justice practice. Paired pre-service student teachers from two diverse university settings, Canada and South Africa, were immersed in a collaborative learning experience that involved exchanges through email, text messages, and artwork collages. As lecturers, we implemented action research to determine how to foster critical reflection by pre-service teachers from diverse education contexts. We anticipated the diverse contexts to serve as a disrupting incident in support of critical reflection and possibly also transformative learning. Findings confirm that the collaborative reflective learning across contexts supported the development of critical reflective skills and provided an opportunity for students to confront their own assumptions of ethical and moral teaching practice. Revised strategies are suggested to support deeper critical reflections in collaborative learning across teaching contexts to support transformative learning.